2000
DOI: 10.1002/1520-6394(2000)12:3<144::aid-da6>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional neuroimaging of electroconvulsive therapy and transcranial magnetic stimulation

Abstract: Neuroimaging has long been utilized to provide a measure of the effects of electroconvulsive therapy (ECT) on brain structure and function as well as to better understand its mechanisms of action. In a similar fashion, functional neuroimaging may provide the means to elucidate both the underlying neurobiological effects and therapeutic potential of transcranial magnetic stimulation (TMS). This article will review findings of neuroimaging studies of both TMS and ECT, concentrating on how such studies may help g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…Less consistency is found regarding the reversibility of abnormalities in rCBF and in cerebral metabolic rate for glucose in depression after electroconvulsive therapy (ECT). Studies that addressed the immediate and acute effects of ECT (e.g., 30 min to 24 h after treatment) disclosed mainly reductions in rCBF and cerebral metabolic rate, whereas when imaging took place some days after ECT, reversal of major depressive disorder (MDD) abnormalities was often found (7)(8)(9). Still, even when imaging was performed at the later stage, reductions (10) or no change (11) in rCBF or cerebral metabolic rate were noted.…”
mentioning
confidence: 99%
“…Less consistency is found regarding the reversibility of abnormalities in rCBF and in cerebral metabolic rate for glucose in depression after electroconvulsive therapy (ECT). Studies that addressed the immediate and acute effects of ECT (e.g., 30 min to 24 h after treatment) disclosed mainly reductions in rCBF and cerebral metabolic rate, whereas when imaging took place some days after ECT, reversal of major depressive disorder (MDD) abnormalities was often found (7)(8)(9). Still, even when imaging was performed at the later stage, reductions (10) or no change (11) in rCBF or cerebral metabolic rate were noted.…”
mentioning
confidence: 99%
“…Some authors, however, found that there may be an association between the excitability of the prefrontal and motor cortex, suggesting that MT determination could be preserved (Kahkonen et al 2004). An alternative to the motor measure is to calculate the dose based on a formula which takes into account the individual distance from scalp to prefrontal cortex (measured with MRI) and the exponential drop in magnetic field strength with increasing distance from the coil Kozel et al 2000;Nobler et al 2000;McConnell et al 2001). The influence of different stimulation frequencies (1Á/20 Hz) is closely related to laterality in brain mood systems, as discussed above.…”
Section: Meta-analysesmentioning
confidence: 93%
“…Deeper situated neurons probably can become activated indirectly via cortical interconnections and redundant cortical Á/subcortical loops. Functional neuro-imaging studies, hormonal changes and changes in brain metabolism after TMS support this hypothesis (Alexander et al 1986;George et al 1996b;Bohning et al 1999;Nobler et al 2000;George et al 2002George et al , 2003.…”
Section: Standard Procedures Tms In Psychiatrymentioning
confidence: 99%
See 1 more Smart Citation
“…Eine kürzlich erschienene Studie,die mit der 133 Xe-Inhalationstechnik an depressiven und manischen Patienten durchgeführt wurde,zeigte erstmalig, dass die Reduktion des CBF in präfrontalen Regionen 50 min nach einer einzelnen EKT-Behandlung im Vergleich zur Voruntersuchung 30 min vor der EKT mit einem besseren klinischen Ansprechen verbunden war. Durch den Abfall des CBF nach einer EKT konnten 68% der Responder und 85% der Nonresponder korrekt klassifiziert werden [30]. Damit könnte die Unterdrückung des zerebralen Blutflusses direkt nach einer EKT einen Prädiktor für den Therapieerfolg mit einer EKT-Serie darstellen.…”
Section: Funktionelle Untersuchungenunclassified